DNA methylation and chromatin accessibility profiling of mouse and human fetal germ cells - Guo, Hongshan; Hu, Boqiang; Yan, Liying; Yong, Jun; Wu, Yan; Gao, Yun; Guo, Fan; Hou, Yu; Fan, Xiaoying; Dong, Ji; Wang, Xiaoye; Zhu, Xiaohui; et al. (Cell research, 2017)
Chromatin remodeling is important for the epigenetic reprogramming of human primordial germ cells. However, the comprehensive chromatin state has not yet been analyzed for human fetal germ ceils （FGCs）. Here we use nucleosome occupancy and methylation sequencing method to analyze both the genome-wide chromatin accessibility and DNA methylome at a series of crucial time points during fetal germ cell development in both human and mouse. We find 116 887 and 137 557 nucleosome-depleted regions （NDRs） in human and mouse FGCs, covering a large set of germline-specific and highly dynamic regulatory genomic elements, such as enhancers. Moreover, we find that the distal NDRs are enriched specifically for binding motifs of the pluripotency and germ cell master regulators such as NANOG, SOX17, AP2γ and OCT4 in human FGCs, indicating the existence of a delicate regulatory balance between pluripotency-related genes and germ cell-specific genes in human FGCs, and the functional significance of these genes for germ cell development in vivo. Our work offers a comprehensive and high-resolution roadmap for dissecting chromatin state transition dynamics during the epigenomic reprogramming of human and mouse FGCs.